Materials for Renewable and Sustainable Energy - Traversa, Enrico
MATERIALS FOR RENEWABLE AND SUSTAINABLE ENERGY is a peer-reviewed open access journal published under the SpringerOpen brand. Energy is the single most valuable resource for human activity and the basis for all human progress. Materials play a key role in enabling technologies that can offer promising solutions to achieve renewable and sustainable energy pathways for the future. MATERIALS FOR RENEWABLE AND SUSTAINABLE ENERGY has been established as an Open Access journal to be the world's foremost interdisciplinary forum for publication of research on all aspects of the study of materials for the deployment of renewable and sustainable energy technologies. MATERIALS FOR RENEWABLE AND SUSTAINABLE ENERGY covers experimental and theoretical aspects of materials and prototype devices for sustainable energy conversion, storage, and saving, together with materials needed for renewable fuel production. Topics include: MATERIALS for renewable energy storage and conversion  Batteries  Supercapacitors  Fuel cells  Hydrogen storage  Photovoltaics and solar cells MATERIALS for renewable and sustainable fuel production  Hydrogen production and fuel generation from renewables (catalysis)  Solar-driven reactions to hydrogen and fuels from renewables (photocatalysis)  Biofuels  Carbon dioxide sequestration and conversion MATERIALS for energy saving  Thermoelectrics  Novel illumination sources for efficient lighting  Energy saving in buildings MATERIALS modeling and theoretical aspects Advanced characterization techniques of MATERIALS MATERIALS FOR RENEWABLE AND SUSTAINABLE ENERGY publishes reviews, original research articles, rapid communications, and perspectives. All manuscripts are peer-reviewed for scientific quality. MATERIALS FOR RENEWABLE AND SUSTAINABLE ENERGY is an Open Access journal supported by King Abdulaziz City for Science and Technology.